IMPLEMENTATION OF THE WAYGROUND APPS AS EVALUATING TEACHING AND LEARNING TOOL OF INTERNATIONAL MUSIC APPRECIATION SUBJECT FOR 8th GRADER SMPN 29 BANDUNG - Liawati Fitriani; Sandie Gunara; Febbry Cipta (Universitas Negeri Medan, 2026)
This study aims to analyze the use of the “Wayground” app as an assessment tool for foreign music appreciation among eighth-grade students at SMPN 29 Bandung and to examine its impact on the quality of learning assessment. This study employs a qualitative approach using the case study method. The research subjects consisted of 28 students who participated in the “Wayground”-based assessment. Data were collected through interviews with teachers and students, observations of the evaluation process in the classroom, and documentation of assessment results recorded in the application. The results of the study indicate that prior to the use of “Wayground,” teachers had utilized various forms of assessment, including digital media; however, their implementation had not been consistent or systematic. The use of the “Wayground” application introduced a more organized assessment process through features such as time management, automatic grading, and the presentation of assessment results in a visual and structured manner. In addition to enhancing students’ motivation, focus, and engagement in completing assignments, this application also supports improved assessment quality through the efficiency of the assessment process, the speed of providing feedback, and the ease with which teachers can document and analyze student learning outcomes more accurately. Thus, the “Wayground” app is considered capable of supporting the implementation of foreign music appreciation learning evaluations that are more effective, systematic, and adaptive to technology-based learning needs. Further research is recommended so that teachers can develop more systematic evaluation plans and integrate the use of the “Wayground” app with appropriate learning strategies to ensure learning outcomes can be measured more optimally. Keywords: Wayground; Music; Digital Assessment; Gamification,